Human Factors and Ergonomics and the management of existential threats: A work domain analysis of a COVID‐19 return from lockdown restrictions system. Issue 4 (6th April 2021) - Salmon, Paul M.; Stevens, Nicholas; McLean, Scott; Hulme, Adam; Read, Gemma J. M.
Abstract: Following strict "lockdown" restrictions designed to control the spread of the COVID‐19 virus, many jurisdictions are now engaged in a process of easing restrictions in an attempt to stimulate economic and social activity while continuing to suppress virus transmission. This is challenging and complex, and in several regions, new outbreaks have emerged. We argue that systems Human Factors and Ergonomics methods can assist in understanding and optimizing the return from lockdown. To demonstrate, we used work domain analysis to develop an abstraction hierarchy model of a generic "return from lockdown restrictions" system. The model was assessed to identify (a) issues preventing a successful return from lockdown; and (b) leverage points that could be exploited to optimize future processes. The findings show that the aim of continuing to suppress virus transmission conflicts with the aims of returning to pre‐virus economic and social activity levels. As a result, many functions act against each other, ensuring that the system cannot optimally achieve all three of its primary aims. Potential leverage points include modifying the goals and rules of the system and enhancing communications and feedback. Specifically, it is argued that moderating economic aims and modifying how social and community activities are undertaken will result in longer term suppression of the virus.